2014
DOI: 10.5914/tropocean.v42i1.5783
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of Calanopia americana Dahl F., 1894 (Copepoda, Calanoida) in a reef environment in tropical Brazil

Abstract: The present study aimed to analyze variations in population dynamics of the Copepoda Calanopia americana (C. americana) in a reef area in tropical Brazil. Diurnal and nocturnal samples were collected at a fixed station during ebb tide, over four lunar cycles, and in the dry and rainy seasons. C. americana presence was very frequent (94%) and occurred in nearly all samples. Overall, juveniles presented higher densities than adults, and females were more abundant than males. There was a significant difference (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…This species makes vertical migrations in both shallow coastal environments and in deeper locations, being more frequently found in surface waters at night compared to day period (Clarke, 1934;Bowman, 1971;Turner et al, 1979;Cohen and Forward, 2002;Melo et al, 2010;Pessoa et al, 2014). The high abundance of C. americana in diurnal samples of FNA could be explained by hydrodynamic effects since the stations are shallow.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This species makes vertical migrations in both shallow coastal environments and in deeper locations, being more frequently found in surface waters at night compared to day period (Clarke, 1934;Bowman, 1971;Turner et al, 1979;Cohen and Forward, 2002;Melo et al, 2010;Pessoa et al, 2014). The high abundance of C. americana in diurnal samples of FNA could be explained by hydrodynamic effects since the stations are shallow.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies that performed daytime sampling this species is cited (Dias and Bonecker, 2009;Dias et al, 2010), but rarely with high abundance (as recorded in the present work). However, high values of abundance have already been recorded for C. americana in nocturnal sampling (Melo et al, 2010;Pessoa et al, 2014). This subgroup also included the Paracalanidae (Acrocalanus longicornis, Calocalanus pavo and Paracalanus aculeatus), a family of great importance in terms of abundance, biomass and daily production, besides being highly adapted to the oligotrophic conditions and having the ability to exploit other forms of food besides the phytoplankton (Miyashita et al, 2009;Melo Júnior et al, 2016).…”
Section: Functional Features Of the Copepod Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations were made in previous studies in the southern part of the Suez Canal and the southern Red Sea by Gurney (1927) and Pesta (1941), respectively, who reported that C. media was found in high abundance in the coastal waters mainly in the night samples. This pattern was recorded also for C. americana F. Dahl, 1894 in the eastern Gulf of Mexico (Turner et al 1979) and in the Brazilian waters (Pessoa et al 2014). This DVM may Table 2.…”
Section: Discussionmentioning
confidence: 52%
“…Of the pontellid copepod genera, Calanopia Dana, 1853, are known to live within reefs (Clarke 1934;Heidelberg et al 2004;Nakajima et al 2008;Pessoa et al 2014). Most other pontellid genera are considered either oceanic or neritic and also neustonic (Silas and Pillai 1973;Conley and Turner 1985).…”
Section: Introductionmentioning
confidence: 99%